THE COMPARATIVE ANALYSIS OF HARMONIC HEARING DEVELOPMENT CONCEPTIONS BY DIFFERENT AUTHORS - Zavadska, Gaļina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Musical-pedagogical theory and practice of higher education have to address complicated issues: the content of musical education changes, new music teacher training forms develop, technical provision of a teaching process improves.Choral singing as a kind of collective music making is an integral component of Latvian culture, an irreplaceable and over centuries tried out factor of spiritual and creative development of a Latvian people. Harmonic hearing is one of the components of musical hearing. The aim of the paper: to present the analysis of works by different authors on issues of the development of harmonic hearing made on the basis of the criteria developed for the analysis of literature. The general pedagogical criteria for the evaluation of teaching aids and the didactic principles of content development from the methodological recommendations “The Development and Evaluation of the Content of Teaching Aids Complying with National Education Standards” (The Department of Pedagogy at the Faculty of Pedagogy and Psychology of the University of Latvia) were taken as a basis for the offered criteria of the analysis of methodological literature.